AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN TWILIGHT SAGA POEM BY STEPHENIE MEYERS - Pratiwi Rusadi, Ni Made; Pratiwi, Desak Putu Eka; Santika, I Dewa Ayu Devi Maharani (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTLiterary work is a work in which the writer aims to present her work that has anaesthetic impression. There are literary works such as prose, poetry or drama. To make a poemmore beautiful and easy to understand, a writer needs to understand the rules of making a goodpoem. This study aimed to analyze the types of figurative language found in Twilight Saga’sPoem and the meaning of the figurative language found in Twilight Saga’s poems. The datawere taken from the Twilight Saga poem adapted from the novel of Stephanie Meyers. Thedata were collected by using observation methods with the following steps: downloading andreading the poem, and then selecting the data which use figurative language. The data wereanalyzed by using qualitative method. Regarding the analysis, there are two theories used inthis research: theory of Figurative Language by Perrine (1977) and theory of Meaning by Leech(1981). For the results, there was found 17 data, includes: simile (2 items or 12,5%), metaphor(1 items or 6,3%), personification (2 items or 12,5%), synecdoche (2 item or 12,5%), symbol(4 items or 25%), hyperbole (3 item or 18,7%) and irony (2 item or 12,5%). The dominanttypes of figurative language are symbol and hyperbole because the author places moreemphasis in choosing beautiful words to make the poems more interesting and meaningful.Keywords: figurative language, meaning, poemABSTRAKKarya sastra adalah suatu karya yang bertujuan untuk menyajikan karyanya yangberkesan estetik, ada karya sastra seperti prosa, puisi atau drama. Agar puisi lebih indah danmudah dipahami, penulis perlu memahami aturan pembuatan puisi yang baik. Penelitian inibertujuan untuk menganalisis jenis bahasa kiasan yang ditemukan dalam Puisi Twilight Sagadan makna bahasa kiasan yang terdapat dalam puisi Twilight Saga. Data ini diambil dari puisiberjudul Twilight Saga yang diadaptasi dari novel Stephanie Meyers. Metode yang digunakandalam penelitian ini adalah metode kualitatif dengan menyajikan gambaran data.Pengumpulan data dilakukan dengan metode observasi dengan langkah-langkah sebagaiberikut: mengunduh dan membaca puisi, kemudian memilih data yang menggunakan bahasakiasan. Dalam analisis data, ada dua teori yang digunakan dalam penelitian ini yaitu teoriFigurative Language oleh Perrine (1977) dan teori Meaning oleh Leech (1981). Dari hasilpenelitian didapatkan 17 data yang meliputi: simile (2 items or 12,5%), metaphor (1 items or6,3%), personification (2 items or 12,5%), synecdoche (2 item or 12,5%), symbol (4 items or25%), hyperbole (3 item or 18,7%) and irony (2 item or 12,5%). Jenis bahasa kiasan yangdominan adalah simbol dan hiperbola karena penulis lebih menekankan pada pemilihan katakatayang indah untuk membuat puisinya menjadi menarik dan penuh makna.Kata Kunci: bahasa kiasan, makna, puisi